Health-related Quality of Life Outcomes of Adalimumab for Patients With Rheumatoid Arthritis in Korea - Lee, Myeung-su; Lee, Chang Hoon; Lee, Hye Soon; Sung, Yoon-Kyoung; Choi, Jung Ran; Park, Kyungsu; Lim, Mi-Kyoung; Choi, Byoong Yong; Kim, Hyoun-Ah; Choi, Seung Won; Lee, Yusun; Yoo, Wan-Hee (Journal of rheumatic diseases, 2021)
Rheumatoid arthritis (RA) is a chronic, progressive, autoimmune disorder that impairs patients' overall health-related quality of life (HRQOL) In this study, we evaluated the effect of adalimumab in Korean patients with active RA on HRQOL. Patients included in the study had moderate to severe active RA that did not respond to conventional drugs with a Disease Activity Score of 28 joints >32 and were biologics-naïve All patients received adalimumab 40 mg subcutaneously every other week and were followed for 24 weeks The primary endpoint was the change in baseline Health Assessment Questionnaire Disability Index (HAQ-DI) score at week 24 Secondary endpoints were changes in the EuroQol 5-dimension 3-Level (EQ-5D-3L) baseline score and Short Form 36-Item Health Survey (SF-36) domain scores at weeks 12 and 24 and change in baseline HAQ-DI score at week 12. In total, 91 Korean patients were included Ninety-three percent of patients were in high disease activity with a baseline mean DAS28 value of 61 within all patients The mean change from baseline in HAQ-DI scores were -046 at week 12 and∼067 at week 24 (p<00001) Additionally, EQ-5D-3L score at weeks 12 and 24 had significantly improved (p<00001) compared to baseline SF-36 at weeks 12 and 24 had significantly improved (p<00001, p=00001) compared to baseline. Treatment with adalimumab resulted in significant improvement in HAQ-DI, EQ-5D-3L, and SF-36 scores at 12 and 24 weeks in Korean RA patient.